Determinants of Islamic Bank Profitability: Empirical Evidence from NTB Islamic Bank - Rizal, Rizal; Amran, Elsa Fitri (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2022)
This research aims to analyze the influence of NPF, BOPO and FDR toward ROA on Bank NTB Syariah. This research is a field study with a quantitative approach. The data used in this study is secondary data in the form of Financial Statements in the quarter of 2018 to September 2022 registered with the Financial Services Authority (OJK). This type of research data is panel data that is analyzed using descriptive statistics, classical assumptions and multiple linear regressions. The result of this research shows that NPF affects ROA with signification of 0.007 smaller than α (0.05,) BOPO has no effect toward ROA with significance of 0.485 greater than α (0.05), FDR has no effect toward ROA with significance of 0.485 greater than α (0.05). Simultaneously, NPF, BOPO and FDR have a significant influence toward ROA variables with a significance rate on 0.018 smaller than α (0.05). Further research is expected to add other variables such as assets, financing and DPK and add years of observation in order to get more representative results